(3GdMQH GdGgdjI GddHfGfjI h CReI GdKhQI GdYHjI (B/s - (3aQMGf,UGdM s ((3HjQhJ (B:s (3OGQ GdcJGH ,s, 1979)
(3QDjI fXQjI h SjGSjI h JfXjejI ddKhQI GdYQHjI GSJQGJjLjG h JcJjcjGs
Keywords: (3GdKhQI GddHfGfjIs; (3GdMQH GdCgdjIs